The Adversity management decisions (Journal of Human Sciences, 2023)
The subject of the research is limited to the final administrative decisions issued by the public administrative authorities, with their general authority, and they are decisions that can be challenged by cancellation, and an exception is made to this. In particular, the decisions preventing litigation stipulated by the legislator varied and multiplied, whether this immunization was a legal text, a regulation, or a deadline. During our research, we will address decisions that are protected by a legal text, which may not be challenged by cancellation before the judiciary, including decisions related to appointing or transferring the judiciary and acting workers, and decisions that are immune under (bylaws), including decisions related to municipalities and inclusive decisions against their students. Decisions that have a defect are among the administrative decision defects and make them illegal, but this defect did not reach the extent of seriousness. The process that descends the administrative decision to the level of material work, as this decision arranges legal effects and obliges individuals to respect it as long as it exists and does not cancel it, withdraw it, or rule to cancel it, and we will address the position of the judiciary and jurisprudence regarding these immunized decisions.